Registration of 'FL720' Oat. Issue 1 (27th October 2016) - Babar, M. A.; Blount, A. R.; Barnett, R. R.; Mackowiak, C.; Akond, M.; Harrison, S. A.; Johnson, J. W.; Mergoum, M.; Mason, E.; Murphy, P.; Ibrahim, A. M. H.; Sutton, R.; et al.
Abstract : FL720 (Reg. No. CV‐380, PI 678418), a facultative‐type forage oat ( Avena sativa L.), was co‐developed by the University of Florida and Louisiana State University Agricultural Center and was released in 2014. FL720 was tested under the experimental designation FL0720‐R6. This line was derived from the three‐way cross FL0206FSB‐34‐S1//FL0016‐H1/IL 3555. FL720 was developed using selected bulk breeding method and was selected as an F5:6 head row. The line was evaluated in preliminary, advanced, and regional forage and grain yield trials from 2012 to 2015. It is a mid‐maturing, high‐yielding forage cultivar with excellent potential for early fall forage production. FL720 was observed to be uniform and stable across multiple locations from 2011 to present. FL720 possess a semiprostrate growth habit and tall plant type. The leaves are large and light green in color. The panicles are long with an average of 4.0 seed whorls. FL720 possesses excellent crown rust (CR) and Barley yellow dwarf virus resistance and moderate resistance to stem rust. FL720 is resistant to the prevalent CR virulence combination that has caused significant disease on the most commonly grown oat cultivars across the southeastern United States since 2013. Average late fall and winter forage yield of FL720 was higher than 'LA99016' and was similar to that cultivar in early spring forage production. FL720 has broad environmental adaptation and has performed well in trials conducted in Florida, southern Georgia, Louisiana, Texas, and South Carolina.